The Impact of Technological Advancements on Criminal Law Amidst Global Digitalization - Elisabeth S Telussa; Alynne H Matulapelwa; John D Pasalbessy (CV. Era Digital Nusantara, 2026)
This study analyzes the transformative impact of global digitalization, specifically Artificial Intelligence and the Metaverse, on criminal law doctrines. Utilizing a normative-juridical approach, it critically examines the United Nations Convention Against Cybercrime 2024 as a pivotal yet controversial instrument affecting state sovereignty and human rights through expanded passive personality jurisdiction. The research highlights the